Management of coronary artery perforations during chronic total coronary occlusion percutaneous coronary intervention - Spyridon Kostantinis; Emmanouil S. Brilakis (REC: Interventional Cardiology (English Ed.), 2022)
Coronary artery perforation is one of the most feared complications of chronic total occlusion (CTO) percutaneous coronary intervention (PCI), as it can lead to pericardial effusion, tamponade, hemodynamic deterioration, need for emergency pericardiocentesis or surgery, or death.1 The incidence of perforation is higher in CTO PCI compared with non-CTO PCI, likely due to higher anatomic complexity of CTOs and the use of advanced wiring techniques, such as antegrade dissection and re-entry and retrograde crossing.2 Coronary perforations have traditionally been classified according to severity using the Ellis classification.3 Because perforation location has important implications for management, another key classification of coronary perforations is according to location, as follows: a) large vessel perforation; b) distal vessel perforation; and c) collateral vessel perforation, in either a septal or an epicardial collateral.4 The first step in perforation management is immediate balloon inflation proximal to or at the site of perforation to prevent accumulation of blood in the pericardial space and tamponade. The balloon should be the same size as the perforated vessel and the inflation often last for several minutes unless the patient develops severe ischemic symptoms.5 Large vessel perforations are usually treated with covered stents, such as the PK Papyrus (Biotronik, United States), and the Graftmaster...